DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA LANSIA PENDERITA DIABETES MELLITUS TIPE 2 - Parsita Sentiani, Dewi; T. Eltrikanawati, T. Eltrikanawati; Nindya Taluphyta, Rurry (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Diabetes Mellitus is a chronic disease in the form of metabolic disorders characterized by blood sugar levels that exceed normal limits. One of the indicators for successful control of Type 2 Diabetes Mellitus is compliance with taking medication accompanied by family support. The purpose of this study was to determine the relationship between family support and adherence to taking medication in elderly people with Type 2 Diabetes Mellitus in the working area of the Sei Langkai Community Health Center, Batam City in 2023. This study included analytic observational research with Case Control design. The sampling technique used was Non-Probability Sampling with Purposive Sampling technique. the number of samples was 88 elderly people from a population of 34,638 elderly people in the Sei Langkai Health Center Working Area of Batam City. This study found the results of good family support with high medication compliance as many as 32 elderly (69.6%) and poor family support with low medication compliance as many as 17 elderly (65.4%). The chi-square test results obtained a value (P-value 0.014 0.05) so that Ha is accepted and H₀ is rejected. So it is concluded that there is a relationship between family support and adherence to taking medication in the elderly with Type 2 Diabetes Mellitus in the working area of the Sei Langkai Health Center in Batam City in 2023. So that family support is needed in determining adherence to taking medication for patients with Type 2 Diabetes Mellitus because the better the family support provided, the better the family support provided.Keywords: DM Type 2, Family Support, Medication Adherence